1977
DOI: 10.1094/phyto-67-101
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Erwinia amylovora Bacteriophage from Aerial Parts of Apple Trees

Abstract: Populations of Erwinia amylovora bacteriophage greater a spreading translucent halo and a smaller plaque without a than 106 plaque-forming units (PFU) per gram of tissue were halo. Thirty-five bacterial isolates, consisting of nine genera, isolated without enrichment from diseased aerial parts of 18 species, and 15 strains of E. amylovora were typed; the apple trees during the summer of 1975. Three phage isolates phages lysed only E. amylovora. The burst size of the three were selected from different geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 0 publications
1
29
2
Order By: Relevance
“…AJ278614) and three ORFs were identified: one encoded an exopolysaccharide depolymerase (Kim & Geider, Ritchie & Klos (1977).…”
Section: Sequence Analysis Of Orf178 and Orf119mentioning
confidence: 99%
See 1 more Smart Citation
“…AJ278614) and three ORFs were identified: one encoded an exopolysaccharide depolymerase (Kim & Geider, Ritchie & Klos (1977).…”
Section: Sequence Analysis Of Orf178 and Orf119mentioning
confidence: 99%
“…Bacteriophages have been used for identification of plant-associated bacteria, to determine capsulation of Erw. amylovora cells and also for disease control (Billing, 1960;Bernhard et al, 1993;Schnabel & Jones, 2001); they have been isolated from the soil in the vicinity of diseased trees (Ritchie & Klos, 1977) and from diseased tissue of host plants (Okabe & Goto, 1963). A bacteriophage was applied to pear slices and it delayed symptom development after inoculation with Erw.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on whether one or multiple host bacterium isolates or species are used for phage isolation, one can obtain phages that are either host specific or display a wide host response range. Ritchie and Klos [55,56] used a single host strain for isolation of phages and reported that the tested E. amylovora phages isolated from aerial parts of apple trees had a narrow host range, as they were able to lyse only isolates of E. amylovora and the closely related saprophyte, P. agglomerans. On the other hand, Gill et al [57] found that phages isolated using a mixture of multiple host strains had a broader host range.…”
Section: Isolation Of Phagesmentioning
confidence: 99%
“…Since the 1970s, more and more phages have been isolated and subsequently characterized in detail [54][55][56][57][58][59][60][61]. However, until recently, numerous efforts to control fire blight in orchards failed because phage populations declined in the absence of E. amylovora [23,56,58].…”
Section: Phages Combined With Other Microorganisms or Applied As Phagmentioning
confidence: 99%
See 1 more Smart Citation